Новые виды цикадовых (Homoptera, Delphacidae) с юга СССР - Логвиненко, В.Н. (Вестник зоологии, 1972)
Three new species of Delphacidae: Ditropis pontica sp. n., Eurybregma striiirons sp. n. and Xanthodelphax optimus sp. n. are described. Distinguishment of these species as new ones is based, besides external features, on a complex of distinct morphological characters in structure of male genitals and in some cases of female ones too.